Exposure of Murattal Al-Quran Audio Enhances Cisplatin Activity on Growth Inhibition and Cell Cycle Modulation on Hela Cells - Mutiah, Roihatul; Mustofa, Muhammad Ragib; Indrawijaya, Yen Yen Ari; Hakim, Abdul; Annisa, Rahmi; Susanti, Nurlaili; Nashichuddin, Ach; Zainuddin, Muhammad (Indonesian Journal of Cancer Chemoprevention, 2019)
Cancer is a disease characterized by abnormal cell mechanisms. The development of alternative cancer treatments is still needed. One of them is the music therapy. The music therapy uses sound vibrations to improve healing. Al-Quran, the Holy book of muslims, recites with measured recitation produces beautiful tones. Reading and recitating of Al-Quran is an important form of worship for which a Muslim can expect reward and benefit in the Hereafter. Al-Fatihah is one of surahs in Al-Qur'an that is often read by Muslims and used as a prayer for healing. The purpose of this study was to determine the effect of cytotoxic activity and cell cycle modulation on Hela cells with exposure of murattal Al-Quran and cisplatin combination. Audio exposure murattal Al-Fatihah and its combination with cisplatin to HeLa cells were tested using the MTT method assay. Induction of apoptosis and modulation of cell cycle evaluated by flow cytometry method. Treatment used 30 minutes Audio Murattal (AM), Cisplatin 10 µg/mL (Cis), and the combination of AM + Cis caused a decrease in the viability of HeLa cells respectively 80.14%, 69.86%, and 64.32%. The results of flow cytometry explained that in treatment of AM there was inhibition in the G2-M phase and induction of apoptosis in the M5 phase. Whereas in treatment AM + Cis inhibition occurs in the S, G2-M phase, and induction of apoptosis in the M5 phase. Audio Murattal Al-Quran presents cytotoxic effects on HeLa cells and to provide a synergistic impact on cisplatin so that disclosure therapy murattal can be recommended for supporting therapy in the treatment of cancer (supportive therapy).Keywords: Al-Quran, Audio murottal, HeLa Cells, Cell Viability, Flow cytometry